Ceramic Water Filters as a Response Technology to Geo-Hazards - E. McBean; G. Huang; Yongping Li; Yanfeng Li; Aili Yang; Haiyan Fu (The Global Environmental Engineers, 2018)
Geo-hazards, a collective term for earthquakes, floods, windstorms, famine and drought, are intensifying with time and are obstacles to attainment of sustainable development. In particular, issues of availability of safe water are major disruptive elements causing the spread of diarrheal diseases during, and post, these geo-hazard events. Given that ceramic water filters (CWFs) have been shown to effectively remove E.-coli (and, by similar attributes, is effective in the removal of cholera), CWFs as a Point-of-Use (POU) technology are described as an effective option for the post-disaster phase of geo-hazards. As described herein, important dimensions of CWFs are provided, showing they can be stored effectively without suffering deterioration, are inexpensive, and are an easy technology to explain to users. Pertinent rationale for serious consideration of CWFs as a post-disaster POU is provided.